4
$\begingroup$

Let $R:=\mathbb{Z}_p[C_{p^\infty}]$ be the group ring of a Prufer group over the field of integers module a prime $p$.

We have $C_{p^\infty}=\langle u_1, u_2, ..., u_n, ... |\,\,\,\, u_1^p=1,\,\,u_{i+1}^p=u_i,\,\,\, i=1,2,...\rangle$.

$(u_{k}-1)^m=0$ if and only if $m\geq p^{k}$.

I solved one implication ($m\geq p^{k}$ implies $(u_{k}-1)^m=0$) but I cannot get the other.

About the other implication.

If $(x-1)^m=0$, then taking the minimum $n\in \mathbb{N}$ such that $m\leq p^n$ we find that $(x-1)^{p^n}=(x^{p^n}-1)=0$ and hence that $n\geq k$. Hence we can assume that $p^{k-1}<m<p^k$.

If $m$ is not coprime with $p$ then $m=p^ch$ and $h<p^{k-c}$. Then (working by induction on the order of $x$) from $0=(x-1)^{p^ch}=(x^{p^c}-1)^h$ we deduce that $h\geq p^{k-c}$ that is absurd. Hence we can also assume that $m$ is coprime with $p$.

$\endgroup$
  • 1
    $\begingroup$ For the first problem: note that if $x^m = 0$ in a ring, then $x^{p^n} = 0$ for some $n$ (just pick $n$ large enough that $p^n\geq m$. $\endgroup$ – Tobias Kildetoft Mar 28 '14 at 11:54
  • $\begingroup$ I wrote "assume for simplicity" because I was thinking at some generalization of it, but maybe it will be better without it. About the first problem, I don't get your suggestion. The $k$ is fixed in my statement: $p^k$ is the order of $u_k$. I want to prove that $(u_k-1)^m=0$ implies that $m$ must be greater than $p^k$. Have I misunderstood? $\endgroup$ – W4cc0 Mar 28 '14 at 12:01
  • 1
    $\begingroup$ So, you have that it is $0$ for some $m$, and hence that it is $0$ for some $p^n$. Now go back to conclude that $n\geq k$. $\endgroup$ – Tobias Kildetoft Mar 28 '14 at 12:02
  • $\begingroup$ I think I get it now: we have to take the minimum $n$ such that $m\leq p^n$ and then we have the result by contradiction because $(u_k-1)^{p^n}=(u_k^{p^n}-1)$ which is different from $0$ when n is strictly lower than $k$. Thanks! (If I understood that well) $\endgroup$ – W4cc0 Mar 28 '14 at 12:07
  • $\begingroup$ Yes, precisely. $\endgroup$ – Tobias Kildetoft Mar 28 '14 at 12:10
1
$\begingroup$

Let $m \ge 0$. Write $$ m = \sum_{i=0}^{\ell} a_i p^i, \quad 0 \le a_i < p, \quad a_{\ell} > 0. $$ This decomposition is just $m$ in base $p$, thus is unique. It follows that $$ (u_k-1)^m = (u_k-1)^{\sum_{i=0}^{\ell} a_i p^i} = \prod_{i=0}^{\ell} (u_k^{p^i} - 1)^{a_i} = \prod_{i=0}^{\ell} (u_{k-i} - 1)^{a_i}. $$ Since all these factors are zero for $i \ge k$, we see that $(u_k-1)^m = 0$ if $\ell \ge k$, i.e. $m \ge p^k$.

If $m < p^k$, note the interesting fact that since each term in the expansion of $(u_{k-i}-1)^{a_i}$ has the coefficient $\binom{a_i}j (-1)^j$ for $0 \le j \le a_i$ (which is non-zero in $\mathbb Z/p\mathbb Z$), writing $\prod_{i=0}^{\ell} (u_{k-i}-1)^{a_i}$ over the basis you gave for the group ring gives a non-zero term of the form $b u_k^{b_0} \cdots u_{k-\ell}^{b_{\ell}}$ with $0 < b < p$ and $0 \le b_i \le a_i$. In other words, $$ (u_k-1)^m = \prod_{i=0}^{\ell} (u_{k-i}-1)^{a_i} = \prod_{i=0}^{\ell} \left( \sum_{b_i=0}^{a_i} \binom{a_i}{b_i} (-1)^{b_i} u_{k-i}^{b_i} \right) = \underset{0 \le b_i \le a_i}{\sum_{0 \le i \le \ell}} \underset{\neq 0}{\underbrace{\left( \prod_{i=0}^{\ell} \binom{a_i}{b_i} (-1)^{b_i} \right) }}\left( \prod_{i=0}^{\ell} u_{k-i}^{b_i} \right). $$ The basis elements $\left( \prod_{i=0}^{\ell} u_{k-i}^{b_i} \right)$ being linearly independent, you see that $(u_k-1)^m \neq 0$.

Hope that helps,

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.